Regulation of Social Recognition Memory in the Hippocampal Circuits - Wang, Xinnian; Zhan, Yang (Frontiers in Neural Circuits, 2022)
Social recognition memory is a kind of brain social internal state, in which social animals recognize and remember familiar individuals of the same species. Substantial research has shown that social recognition memory is valuable and beneficial to all mammals because social recognition memory is essential even when animals conduct daily social activities. This brief review summarizes a brain network about social recognition memory and then explores the possible relationship between social isolation and social recognition memory. Finally, we introduce some possible related molecular mechanisms underlying social recognition memory. These findings help us explore potential targets of social deficit diseases.